Mediastinoscopy Conventional and Video Surgery - Delbene, Roberto; Arévalo, Carlitos; Olivera, Eduardo (Cirugía del Uruguay, 2004)
Tise retrospective analysis covers 47 mediastinoscopies with a predominantly etio/ogic diagnosis of /ung cancer and lymphomas. Sensitivity was very high (98%) and specificity was 100%. There was one complication regarding an airway which /ead to open surgery and two bleedings which had no consequences. Mortality was ni/. The authors are now currently performing video mediastinoscopies with the advantage of better visualization, participation of the who/e team and documentation of procedure.